Analisis Pengaruh Belanja Daerah Bidang Pendidikan, Bidang Kesehatan dan Bidang Infrastruktur terhadap Indeks Pembangunan Manusia di Kabupaten Hulu Sungai Utara Tahun 2003-2015 - Fahrianti, Sippa; Saleh , Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
In general, the Human Development Index (HDI) can be interpreted as a method used to measure the success or failure of a country or region in the field of human development. Then to increase progress and reduce gaps in regional development, regional development programs must be well planned and use principles in enhancing human development. The purpose of this study was to determine the effect of regional spending in education, in health and in infrastructure in the human development index in Hulu Sungai Utara Regency. The research method used in this study is a multiple linear regression model that has more than one estimating variable, namely X1, up to X3 with the classic assumption test including normality test, heteroscedasticity test and hypothesis testing. From the results of the study indicate that there is a significant positive influence of regional expenditure on education in the Human Development Index of 20.8%. This positive effect means that if regional expenditure in the field of education gets better then the Human Development Index will also increase, and so will the regional expenditure in the health sector towards the Human Development Index significantly influence by 34%. And regional spending in the infrastructure sector also significantly influences the Human Development Index, which is 27.2%. This influence means that if regional spending in education, health and infrastructure is getting better, the Human Development Index (HDI) will also increase.